Impacts of land use change brought by coastal land reclamation projects (1990-2020) in Manila, Pasay, Parañaque on economic development, community, and government - Discar, Giany Marxiamille C.; Gomez, Jose Edgardo A. Jr. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2025)
Over the past thirty years, coastal land reclamation projects (CLRPs) have shaped the urban landscape of Metro Manila, particularly in the cities of Manila, Pasay, and Parañaque. Despite their growing prevalence, local research on CLRPs remains limited, especially regarding their implications for real estate planning and development. This study addresses that gap through a thematic analysis of CLRPs built from 1990 to 2020. It evaluates their impacts on three interrelated dimensions: local economic development, community well-being, and governance.

Findings show that CLRPs have stimulated urban economic activity by facilitating the development of commercial, residential, and institutional spaces, driven by public-private partnerships. These developments helped boost local economies and state revenues, but disproportionately served higher-income populations. While framed as engines of modernization, CLRPs have also triggered adverse consequences, such as the displacement of coastal communities and the loss of traditional livelihoods. These outcomes highlight the disconnect between the narrative of inclusive development and the lived realities on the ground.

Governance analysis reveals that while the policies of the Philippine Reclamation Authority (PRA) and the Philippine Environmental Impact Statement System (PEISS) introduced regulatory measures, implementation and accountability remain inconsistent. On the other hand, Local Government Units (LGUs) possess autonomy but often lack the foresight and institutional capacity to guide equitable CLRP outcomes. As a result, policy responses have largely been reactive, reinforcing private sector dominance over planning processes.

This study proposes a tri-sectoral approach of examining CLRPs, through the lenses of local economic development, community well-being. and governance. Key recommendations include adopting a national or regional Reclamation and Development Plan (RDP) and integrating planning for CLRPs into the Comprehensive Land Use Plans (CLUPs) of LGUs, thereby strengthening community engagement. Such reforms can ensure that CLRPs contribute not only to economic growth but also to sustainable and inclusive urban development.
Thesis
Keywords: Reclamation of land -- Philippines -- Manila; Land use -- Philippines -- Manila; City planning -- Philippines -- Manila; Reclamation of land -- Philippines -- Pasay; Land use -- Philippines -- Pasay; City planning -- Philippines -- Pasay; Reclamation of land -- Philippines -- Parañaque; Land use -- Philippines -- Parañaque; City planning -- Philippines -- Parañaque